Tandem Rh-Catalysis: Decarboxylative β-Keto Acid and Alkyne Cross-Coupling - Cruz, Faben A. (Chem Commun (Camb), 2016)
Herein, we describe a regioselective Rh-catalyzed decarboxylative cross-coupling of β–keto acids and alkynes to access branched γ,δ–unsaturated ketones. Rh-hydride catalysis enables the isomerization of an alkyne to generate a metal-allyl species that can undergo carbon-carbon bond formation. Ketones are generated under mild conditions, without the need for base or activated electrophiles.